PENINGKATKAN PEMAHAMAN KOSA KATA MELALUI DESAIN KELAS LITERAT KELAS III TUNAGRAHITA SLB NEGERI 1 MATARAM TAHUN 2018 - Kamtono Kamtono (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2021)
Abstract Literate class design is a literate class environment that is arranged in such a way that it is rich in linguistic media. Children with special needs require special handling by maximizing a literate classroom design. Language is very closely related to literacy because the components in language contained in literacy include reading, writing, listening, and telling stories. Literacy skills in children need to be supported and facilitated by schools. A literate classroom environment is one of the efforts that teachers can make for the achievement of children's language development. The Literate Class Design that has been implemented has had a positive impact on teachers, students, and parents. teaching learning p[rocess which at first arbitrarily now has now carried out learning with full attention and communication with students is more effective and efficient. The previously unorganized classroom arrangement has now attracted more attention and made it easier to control the activities of students and teachers. The occurrence of repetition of learning that is not realized by students without any orders from the teacher every day, just by looking around the class which is deliberately designed with a literate class. Parents are motivated and enthusiastic and fully support participating in designing literacy classes for the progress of their children's learning at school. The aim is to improve the vocabulary comprehension skills of third grade SDLB students through literacy classes at SLBN 1 Mataram. The method used is observation, test, and documentation. The results obtained are that children are accustomed to observing the classroom environment, improving the ability of mentally retarded children to understand vocabularies, getting to know the wider environment, and also increasing students ability to explore their knowledge Keywords: Literate Class Design, Vocabulary Comprehension, Children with Special Needs